Projeto de um sistema de captação de água pluvial para uso não potável em condomínio - Silva, Wallace dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
One of the most important resources for humanity's survival is freshwater, and only a minority is available for human consumption on our planet. Civil construction is one of the most important sectors of the Brazilian economy, and presents a great potential to adopt sustainable practices at large scales. Aiming at the principles of sustainability for new projects and constructions and in view of this scenario of long periods of drought that culminated in the water crisis that has been affecting Brazil in a growing way in the last years, this work had the objective of developing a project for the implementation of a condominium of Houses, in which there will be rainwater harvesting, treatment, storage and reuse of water according to ABNT (Brazilian Association of Technical Standards) standards. The use of rainwater for non-potable purposes as an alternative source of supply contributes to sustainable development, bringing environmental savings and benefits

Um dos recursos mais importantes para a sobrevivência da humanidade é a água doce, e desta apenas uma minoria está disponível para consumo humano em nosso planeta. A construção civil é um dos setores mais importantes da economia brasileira, e apresenta um grande potencial de adotar praticas sustentáveis em grandes escalas. Visando os princípios da sustentabilidade para novos projetos e construções e diante desse cenário de longos períodos de estiagem que culminaram na crise hídrica que vem afetando o Brasil de forma crescente nos últimos anos, este trabalho teve como objetivo desenvolver um projeto para implantação de um condomínio de casas, no qual haverá captação de águas pluviais, tratamento, armazenagem e reuso da água de acordo com as normas da ABNT (Associação Brasileira de normas técnicas). O aproveitamento de águas pluviais para fins não potáveis como fonte alternativa de abastecimento contribui para o desenvolvimento sustentável, trazendo economia e benefícios ambientais
Design of a rainwater harvesting system for non-potable use in condominium
Keywords: Desenvolvimento sustentável; Condomínios; Aguas pluviais; Sustainable development